2021
DOI: 10.2147/ceor.s318589
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Peptide Enhanced Bone Graft i-Factor versus Use of Local Autologous Bone in Anterior Cervical Discectomy and Fusion Surgery

Abstract: We conducted decision analytical modeling using a Markov model to determine the ICER of i-factor compared to autograft in ACDF surgery. Objective: The efficacy and safety of traditional anterior cervical discectomy and fusion (ACDF) surgery has improved with the introduction of new implants and compounds. Costeffectiveness of these innovations remains an often-overlooked aspect of this effort. To evaluate the cost-effectiveness of i-FACTOR compared to autograft for patients undergoing ACDF surgery. Methods: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…43 None of the randomized clinical trials included in this review assessed the cost-effectiveness of biomaterials. However, Thaci et al 55 demonstrated that 15-aminoacid polypeptide bone substitute significantly reduced costs compared to autograft in cervical discectomy and fusion. Nevertheless, the evidence on the cost-effectiveness of biomaterials on orthopedic surgery is limited and warrants further studies.…”
Section: Discussionmentioning
confidence: 99%
“…43 None of the randomized clinical trials included in this review assessed the cost-effectiveness of biomaterials. However, Thaci et al 55 demonstrated that 15-aminoacid polypeptide bone substitute significantly reduced costs compared to autograft in cervical discectomy and fusion. Nevertheless, the evidence on the cost-effectiveness of biomaterials on orthopedic surgery is limited and warrants further studies.…”
Section: Discussionmentioning
confidence: 99%
“…Improved healing and adequate fusion are associated with improved quality of life, faster return to work, less pain, less opiate use, and fewer repeat surgeries. [1] This is in stark contrast properties of native bone. Similarly, radiolucent biomaterials were preferred so that future radiographic interpretation was not hindered.…”
Section: Introductionmentioning
confidence: 95%
“…Improved healing and adequate fusion are associated with improved quality of life, faster return to work, less pain, less opiate use, and fewer repeat surgeries. [1] This is in stark contrast to failed fusions, often due to pseudoarthrosis or subsidence. Failures are associated with costly and often more complicated revisions as well as serious downstream consequences for patients.…”
Section: Introductionmentioning
confidence: 99%
“…The unit cost of i-Factor ranges from $757 to $2090, depending on the size ordered. Thaci et al 12 determined the incremental cost-effectiveness ratio of i-Factor use in ACDFs was $13,333 per quality-adjusted life year at 90 days and demonstrated a greater benefit and a lower cost at 1 year compared with the bone autograft cohort. An analysis comparing the total direct medical costs of BMP found that from a payer perspective, the cost of the utilization of BMP is offset by the reduction of medical resources associated with costs associated with fusion failures and the adverse events associated with ICBG harvest 13 .…”
Section: Cost-utilitymentioning
confidence: 99%